Keeping at Arm’s Length or Searching for Social Proximity? Corporate Social Responsibility as a Reciprocal Process Between Small Businesses and the Local Community - Lähdesmäki, Merja (Journal of business ethics, 2012)
This article examines the relationship between corporate social responsibility and locality in the small business context. This issue is addressed by studying the interplay between small businesses and local community based on the embeddedness literature and using the concept of social proximity. On the basis of 25 thematic interviews with owner-managers a typology is constructed which illustrates the owner-managers’ perceptions of the relationship between the business and the local community. The findings emphasize the importance of reciprocity as it is suggested that corporate social responsibility in relation to locality is constructed as a response to the interpretations of reciprocal community support between small business owner-managers and local community.